NON-ADHERENCE OF PRIMARY CARE PEDIATRICIANS IN SERBIA TO LATEST GUIDELINES FOR THE MANAGEMENT OF ACUTE AND CHRONIC COUGH IN CHILDREN - Milosevic, Katarina; Plavec, Davor; Rsovac, Snezana (Medical Research, 2024)
Introduction: Cough is the most frequent symptom in children and can indicate various pathological conditions. Several international guidelines have been published with a purpose to standardize and improve the assessment and management of cough. Non-adherence to guidelines often leads to a suboptimal quality of patient care. Our aim was to investigate the adherence of Serbian primary care pediatricians to the latest international guidelines on cough diagnosis and management. Methods: The study has included pediatricians working in primary health care centers in Serbia. They were given a questionnaire designed by the team of pulmonologists that included questions about choice of diagnostic and therapeutic approaches for acute and chronic cough. Results: Most of the primary care pediatricians assessed value of international guidelines as fair. However, nearly 70% stated that they prescribe herbal syrup for acute cough. Chronic cough is treated mostly with ivy extract, bronchodilators and antihistamines. Majority of doctors declared positive opinion about herbal medicaments and negative opinion about alternative medicine. About 73% of them stated that they do not use the chest x-ray as a part of diagnostic procedure. Conclusion: Serbian pediatricians do not adhere to international guidelines in relation to diagnosis and treatment of cough. The reasons for non-adherence to guidelines should be further investigated.
Keywords: cough, guidelines, children, primary health care